Hydronephrosis after retroperitoneal laparoscopic dismembered Anderson–Hynes pyeloplasty in adult patients with ureteropelvic junction obstruction: A longitudinal analysis - Isoyama, Tadahiro (Polish Urological Association, 2014)
OBJECTIVE: We evaluated the improvement of hydronephrosis longitudinally after laparoscopic dismembered Anderson–Hynes pyeloplasty in adult patients with ureteropelvic junction obstruction. MATERIAL AND METHODS: Sixteen patients underwent laparoscopic pyeloplasty at our institution between January 2006 and June 2012. Hydronephrosis was assessed by ultrasound and intravenous pyelography at 3, 6, 12, 18, and 24 months after pyeloplasty. RESULTS: The mean follow–up time was 24 months. Preoperative hydronephrosis was diagnosed as grade 2 and grade 3 in 8 patients each. Postoperative improvement of the hydronephrosis by one grade was observed in 56%, 73%, 67%, 50%, and 40% of patients at 3, 6, 12, 18, and 24 months, respectively. Improvement of the hydronephrosis by two grades was observed in 6%, 27%, 33%, 50%, and 60% of patients at 3, 6, 12, 18, and 24 months, respectively. In 5 of 12 patients (42%), hydronephrosis was still improving even after 12 months postoperatively. CONCLUSIONS: Adult patients demonstrate relatively rapid improvements in the degree of hydronephrosis after laparoscopic pyeloplasty and continue to improve for a long time.